Lumberjanes. Volume twelve, Jackalope springs eternal - Watters, Shannon; Leyh, Kat (Boom! Box, 2019)
In order to regroup from the time machine debacle, Jen takes the 'Janes on a little adventure to capture the notorious, elusive, Jackalope.